Pengembangan Pendidikan Karakter di SMA Islam - Fahimul Amri; Hastin Riva Nugraheni (Didaktika : Jurnal Kependidikan, 2021)
Character education is a necessity for schools to be developed, because character education can shape the personality or character of students for the better. This study aims to reveal the development of character education in Roudlotun Nasyiin Islamic High School Mojokerto. This study has used a qualitative descriptive approach to reveal and explain the development of character education that has been implemented in Roudlotun Nasyiin Islamic High School. The main data source of this research is primary data obtained directly from informants, namely the principal, vice principal, teacher, and students. The data collection instrument used interviews. Data validity uses source triangulation. Data analysis is carried out through data reduction, data presentation, and drawing conclusions. The results showed that Roudlotun Nasyiin Islamic High School had developed character education for students. The development of character education is carried out based on the vision and mission set by the school. So that the development of character education is part of efforts to achieve the school's vision and mission. The development of character education is applied using the method of habituation and exemplary. Habituation is carried out in the form of routine, spontaneous, and programmed activities. The development of character education that has been carried out has a positive impact on students, among them students become more understanding of religious values.Keywords: Character education, vision and mission, habituation